Edukasi Konsep Pariwisata Berbasis Masyarakat Untuk Meningkatkan Pemahaman Manajemen Destinasi Siswa SMKN 2 Pariaman Bidang Studi Keahlian Pariwisata - Mariyanti, Eka; Maivalinda, Maivalinda; Abdilla, Mohammad; Sari, Puti Embun; Sukma, Tri; Vanisya, Winda; Caniago, Rita Sri Hasnita; Wandi, Agus; Konceta, Nesa Dela (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
Community-Based Tourism (CBT) is an approach that emphasizes active community participation in managing tourism destinations to create sustainable economic, social, and environmental benefits. This community service program aims to enhance students' understanding of CBT concepts and destination management through interactive education. Activities include socialization, workshops, and evaluations using pre-test and post-test assessments to measure the program's effectiveness. A total of 85 students from the hospitality and culinary fields participated in this program. Evaluation results showed an increase in the average understanding score from 65.4 in the pre-test to 87.2 in the post-test, indicating the effectiveness of the applied learning methods. Additionally, interviews with students and teachers revealed increased awareness of the importance of community involvement in tourism management. This education program not only improved conceptual understanding but also encouraged students' creativity in developing innovative ideas for tourism development in Pariaman City. With enhanced knowledge and awareness of CBT, students are expected to contribute to sustainable tourism management in the future.